Based on Fuzzy Comprehensive Evaluation, the Online and Offline Hybrid Teaching Mode of Physical Education Courses is Constructed. (29th September 2022) - Qian, Xiaodong; Li, Xinhua
Abstract : With the continuous development of the times, the educational concept in the information age continues to advance, in order to meet the needs of the society, each school in China has reformed and piloted according to its own situation to improve the quality of teaching. The research of conventional mixed physical education teaching, from the perspective of research methods, can be divided into two orientations: qualitative and quantitative. On the other hand, from the perspective of sample size, traditional research is a small sample study, and these objective behavioral data have opened up a new perspective for the research of blended physical education teaching from the research methods and research content. In this context, this paper combines the fuzzy comprehensive evaluation method to propose fuzzy comprehensive evaluation methods for mixed physical education teaching, such as preclass preparation, in-class links, teaching content, and teaching methods and designs an online and offline hybrid teaching mode for physical education courses based on a fuzzy comprehensive evaluation to construct an evaluation system, determine its fuzzy operators, determine indicators, and evaluate them comprehensively, reasonably and accurately through experiments. The fuzzy comprehensive evaluation method is based on the fuzzy mathematics comprehensive evaluation method, which can evaluate the evaluation object from all aspects, can objectively reflect the essential characteristics of things, and the evaluation process of the mixed mode construction of physical education courses is more scientific and reasonable. The application of the fuzzy comprehensive evaluation method has effectively promoted the reform and improvement of education and provided a foundation for the continuous improvement and innovation of students' learning and teachers' teaching effects.